Risk Factor Assessment of Multidrug-Resistant Tuberculosis - Pant, R; Pandey, KR; Joshi, M; Sharma, S; Pandey, T; Pandey, S (Journal of Nepal Health Research Council, 2010)
Background: Despite increasing numbers of MDR TB cases seen in Nepal, a lot remains to be understood about the disease in the local context. We evaluated possible risk factors for MDR TB among patients enrolled for treatment at a district hospital in western Nepal. Methods: A descriptive case-series study using structured interviews and abstraction of treatment records of all patients registered at the DOTS Plus clinic at Bhim Hospital, Bhairahawa from April 2008 to Dec 2008 was done. Descriptive analysis was done to find out frequencies and relations. Results: Of the total 31 patients, 22 were males (age range 18-68, median 36.7) and the remaining 9 females (age range 23-56, median 33.7). 27(87%) of the patients had monthly income below Rs 3000 and 24 (77%) of them were illiterate. 21(67%) had missed at least a few weeks of drugs during their previous treatment and 4 (13%) had been marked as defaulters. 6 (20%) had treatment failure. 74% of the patients were smokers, 2 were HIV positive. 20 (58%) had lived in India for at least 6 months where they had incomplete treatment of TB. 30 (97%) patients had disclosed their MDR status to their families; however 70% said they did not do so immediately. Conclusions: Previous TB treatment, male sex, poverty, migration to India, illiteracy and smoking have been observed in a majority of the cases in this study. These findings need to be corroborated with multi-centre casecontrol studies to bring out nationally relevant risk factors for MDR TB. Key words: directly observed treatment short course-plus; multi- drug resistance; risk factors; tuberculosis. DOI: 10.3126/jnhrc.v7i2.3013 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 89-92